1988
DOI: 10.1111/j.1600-0528.1988.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of dental status and treatment behavior among Norwegian adults 1973–85

Abstract: Utilization rates, types of dental services received and reports on number of teeth present were studied through seven sets of cross-sectional data collected in 1973, '77, '79, '81, '83 and '85. Personal interviews performed by trained interviewers were held with nationwide probability samples, each of 1500 persons covering the Norwegian population aged 15 and above. During the 12-yr period, the percentage of the samples reporting to have 20 or more teeth increased from 63 in 1973 to 74 in 1985, while the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 6 publications
6
27
1
4
Order By: Relevance
“…that the incidence of extractions because of caries decreases with age. The changes between 1968 and 1988 might be attributable mainly to period effects, generally improved oral health, improved availability of dental services, and because patients became more reluctant to have teeth extracted for psycho-social reasons (12,13,30). In our quasi-longitudinal study, the period effects might differ inside the cohorts as well as between them.…”
Section: Longitudinal Differencesmentioning
confidence: 82%
“…that the incidence of extractions because of caries decreases with age. The changes between 1968 and 1988 might be attributable mainly to period effects, generally improved oral health, improved availability of dental services, and because patients became more reluctant to have teeth extracted for psycho-social reasons (12,13,30). In our quasi-longitudinal study, the period effects might differ inside the cohorts as well as between them.…”
Section: Longitudinal Differencesmentioning
confidence: 82%
“…The figures found in 1987 were 72, 49 and 40%, respectively, in the age groups of 55, 65 and 75 years, compared with 86, 73 and 46% in 1997. In the Norwegian study, the percentage of those aged 50 and more who reported having 20 or more teeth had increased from 31% in 1973 to 44% in 1985 [Helöe et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…In the repeated cross-sectional study of inhabitants in the city of Jönkö-ping, Sweden, 20 and 37% were found to be edentulous in the age groups of 60 and 70 years in 1973 compared with 10 and 23% in 1993 [Hugoson et al, 2000]. In Norway, the percentage of edentulous persons aged 15 and over dropped from 16 to 12% during the 12-year period from 1973 to 1985 [Helöe et al, 1988]. The prevalence of edentulism decreased from 19 to 6% among Finnish adults of working age between 1978[Suominen-Taipale et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations